2014
DOI: 10.1038/leu.2014.305
|View full text |Cite
|
Sign up to set email alerts
|

Dual PI3K/mTOR inhibition shows antileukemic activity in MLL-rearranged acute myeloid leukemia

Abstract: In acute myeloid leukemia (AML), several signaling pathways such as the phosphatidylinositol-3-kinase/AKT and the mammalian target of rapamycin (PI3K/AKT/mTOR) pathway are deregulated and constitutively activated as a consequence of genetic and cytogenetic abnormalities. We tested the effectiveness of PI3K/AKT/mTOR-targeting therapies and tried to identify alterations that associate with treatment sensitivity. By analyzing primary samples and cell lines, we observed a wide range of cytotoxic activity for inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
76
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 59 publications
2
76
2
1
Order By: Relevance
“…IDH2 mutations, present in 3 of 31 samples in this cohort, had not been detected in previous reports, possibly reflecting a great heterogeneity in this disease. Finally, rare mutations in genes encoding splicing factors have been described in the MLL-MLLT3 subtype 10 . In our cohort, we found three mutations in SRSF2 in non-MLL-MLLT3 samples, indicating that these events occur in various MLL-F ALL subtypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IDH2 mutations, present in 3 of 31 samples in this cohort, had not been detected in previous reports, possibly reflecting a great heterogeneity in this disease. Finally, rare mutations in genes encoding splicing factors have been described in the MLL-MLLT3 subtype 10 . In our cohort, we found three mutations in SRSF2 in non-MLL-MLLT3 samples, indicating that these events occur in various MLL-F ALL subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…The previous analysis, however, showed that MLL-F AMLs have the lowest frequency of mutations among all the AML subtypes 9 . Targeted analyses of larger MLL-F AML cohorts have identified frequent KRAS and NRAS mutations in this disease 7,10 . Consistent with these observations, recent studies have indicated that MLL-F AMLs are possibly more sensitive to mitogen-activated protein kinase kinase (MEK) inhibitors than control leukemias, raising the possibility that the RAS-ERK pathway is sensitized in MLL-F AMLs 11 .…”
mentioning
confidence: 99%
“…34 Notably, there was particular sensitivity among the AML blasts with MLL translocations, a subset in which 52% contained an NRAS or KRAS mutation as compared to 28% in cytogenetically normal AML blasts. 34 These results are in agreement with reports showing that RAS mutations can activate the PI3K/AKT/mTOR pathway. 35 As another example of the regulatory complexity of this pathway, treatment with BEZ-235 resulted in increased phosphorylation of ERK (extracellular regulated kinase) suggesting an escape mechanism for PI3K/AKT/mTOR inhibition.…”
Section: Pi3k (Phosphatidylinositol 3'-kinase)mentioning
confidence: 98%
“…33 The similarities between the PI3K p110 subunit and mTOR catalytic domains have allowed the development of dual PI3K/mTOR dual inhibitors including BEZ-235. 34 BEZ-235 was found to induce significant apoptosis of primary AML blasts to a greater magnitude than the selective AKT and mTOR inhibitors, MK-2206 and rapamycin, respectively. 34 Notably, there was particular sensitivity among the AML blasts with MLL translocations, a subset in which 52% contained an NRAS or KRAS mutation as compared to 28% in cytogenetically normal AML blasts.…”
Section: Pi3k (Phosphatidylinositol 3'-kinase)mentioning
confidence: 99%
See 1 more Smart Citation